2022
DOI: 10.1007/s12144-021-02670-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adolescents’ prosocial experiences and mental health during the COVID-19 pandemic

Abstract: Natural disasters and times of crisis, such as the COVID-19 pandemic, are extremely stressful events, with severe mental health consequences. However, such events also provide opportunities for prosocial support between citizens, which may be related to mental health symptoms and interpersonal needs. We examined adolescents’ prosocial experiences as both actors and recipients during the early stages of the COVID-19 pandemic and assessed whether these experiences were associated with indicators of mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Almost every child reported heightened anxiety, fear, frustration, and exacerbation of existing psychological issues linked to the pandemic and stay at home measures. Similar to previous studies, we learned that adolescent participants started to experience psychological effects such as depression, and anxiety as the lockdowns persisted throughout the pandemic (Alvis et al, 2022;Amran & Jamaludin, 2021). Moreover, the interruption of education, physical activities, and socialization opportunities due to the confinement of children and adolescents were reported to create uncertainty and anxiety for them (Singh et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…Almost every child reported heightened anxiety, fear, frustration, and exacerbation of existing psychological issues linked to the pandemic and stay at home measures. Similar to previous studies, we learned that adolescent participants started to experience psychological effects such as depression, and anxiety as the lockdowns persisted throughout the pandemic (Alvis et al, 2022;Amran & Jamaludin, 2021). Moreover, the interruption of education, physical activities, and socialization opportunities due to the confinement of children and adolescents were reported to create uncertainty and anxiety for them (Singh et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…Despite the many negative effects of the pandemic on mental health in young people identified to date, evidence also suggests that young people’s altruistic motivations45 46 and prosocial behaviours have increased, including providing practical support to others and donating to charities 47. It is encouraging that some participants in this study reported feeling more able to talk about their mental health compared with prepandemic, suggesting less social stigma perceived by young people in this study to be associated with mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies during the pandemic suggest that people can benefit from real-life and online social support (Raude et al, 2020; Skalski et al, 2021; Wright et al, 2021; Yu et al, 2020). Social support increases belongingness and community attachment during the pandemic and that results on reduced anxiety and depressive symptoms (Alvis et al, 2022). Additionally, peer and community support groups reduces psychological distress in the era of pandemic (Nobles et al, 2020).…”
Section: Discussionmentioning
confidence: 99%